Spiritual Approach in Managing Work-related Stress of Academicians. (12th February 2015) - Hamjah, Salasiah Hanin; Ismail, Zainab; Sham, Fariza Md.; Rasit, Rosmawati Mohd.; Ismail, Adawiyah
Abstract: Work-related stress is an imbalance between work-related demand and individual capacity. If not appropriately handled, it may adversely affect individual emotions. Work-related stress is also experienced by academicians in institutions of higher learning due to various aspects. Various measures have been taken by academicians to overcome stress so that it will not adversely affect academic excellence and scholarship. Hence, the aim of this research is to identify the perceptions of academicians regarding their career and to examine the role of the spiritual aspect in managing stress experienced by them. This research is designed as a survey study. 37 out of 108 academicians at the Faculty of Islamic Studies, National University of Malaysia (Universiti Kebangsan Malaysia) have been randomly selected as study sample. Questionnaires are used as instrument of data collection. The data obtained is analysed using the descriptive statistical technique. Research results find that the respondents' perception of their academic career shows they experience stress due to the burden of heavy workload leading to emotional and physical fatigue, and also whenever they receive new assignments. This research also finds that a spiritual approach may play a role in alleviating stress among academicians.